Burn the business plan : what great entrepreneurs really do - Schramm, Carl J. (New York : Simon & Schuster, 2018)
What does it take to start a successful business? Carl J. Schramm, called by The Economist'the evangelist of entrepreneurship,' explains what really matters and what doesn't. Business schools teach the importance of business plans, but Microsoft, Apple, Google, Facebook, and hundreds of smaller, less well-known companies all achieved success long before they had business plans. Here are a few other myths about startups: Contrary to the popular image on entrepreneurs as nineteen-year-olds in college dorm rooms, the average entrepreneur starts his or her company at thirty-nine. The success rate of entrepreneurs over age forty is five times higher than that of entrepreneurs under thirty. Most entrepreneurs have worked for big companies, where they have identified a needed product or service. Their corporate contacts are often their first customers. Many more successful entrepreneurs have studied engineering than business. Fewer than one percent of all startups have venture or angel investors. Burn the Business Plan is filled with stories of successful entrepreneurs. For all of them knowledge, passion, determination, and a willingness to experiment and innovate were far more valuable than financial skill. This book dispels the costly misleading myths that aspiring entrepreneurs believe and offers indispensable real-world advice about how to achieve your dreams. -- from dust jacket
Burn the business plan -- Twelve things every aspiring entrepreneur should know -- Why start a company? -- What motivates entrepreneurs? -- Can you survive the entrepreneur's curse? -- Big companies can be schools for startups -- Copycat entrepreneurs -- Preventing failure before it happens -- Don't waste time doing things that don't work -- Planning for success -- Becoming a successful entrepreneur
Includes bibliographical references : pages 249-255 and index.
Keywords: Entrepreneurship; New business enterprises -- Management; Entrepreneurship; New business enterprises -- Management